Analisis Pengaruh Model Group Investigation Terhadap Kemampuan Berpikir Historis dalam Pembelajaran Sejarah Indonesia - Muhammad Wahyu Adi Nugroho; Arif Permana Putra; Mohammad Ali Fadillah (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze the effect of the group investigation learning model on students' ability to think historically in Indonesian history learning. This research method used a quasi-experimental with a quantitative approach by taking the sample of this study through a non-probability sampling technique, namely students of class XI SMAN 3 Tangerang Regency. The research instrument used tests and data analysis techniques with inferential statistics and t-tests. The results of this study indicated that testing the t-test hypothesis on one side using the polled variant, the results obtained were t-test 3.70, while t-table 1.67. The statistical statement